EXPLORING THE BENEFITS OF FORMATIVE ASSESSMENT IN THE CLASSROOM - I Dewa Ayu Made Meilani Pramesti (Universitas PGRI Palembang, 2023)
Formative assessment is an evaluation technique used in the learning context to track students' progress over time and gauge their grasp of the material. This article employs a library research or literature review methodology. This page describes the many forms of formative assessment that can be applied, including exit tickets, quizzes, peer evaluation, class observations, and more. Because formative evaluation offers so many advantages, it should be carried out. By using formative assessment, teachers may better understand their students' needs and comprehension while also empowering them to take ownership of their education and giving them constructive criticism that helps them advance.